Effect of Zinc Sources and Application Methods on Growth Characteristics, Yield and Nutrients Content in Wheat- Moongbean Cropping System - Manjot Singh,; B.K. Yadav,; Vivek Sharma,; Surjit Singh Minhas,; B.B. Vashist, (Journal of the Indian Society of Soil Science, 2024)
Micronutrient deficiencies have rapidly emerged as a significant human health concern, particularly in developing nations. Zinc (Zn) is a basic ingredient and regulatory co-factor in enzymes and proteins involved in many metabolic activities. It is vital for both animals and plants. Economically, industrial fortification and clinical supplementation are not feasible strategies to combat Zn deficiency at large scale. Enrichment of Zn in wheat grain produced is required to reduce the risk of human Zn deficiency of any area. Therefore, the experiment was conducted during the rabi 2020-21 to study the response of soil and foliar applied Zn on wheat and simultaneously kharif-2021 for its residual effect on moongbean. The results of the present study revealed that plant growth parameters such as plant height, spike length, test weight, grain and straw yield of wheat significantly differ among wheat cultivars and increased by treatment T5 (2.5 kg Zn ha-1 + 0.5% EDTA-Zn along with 1% urea at the time of booting + grain filling stages). Macronutrients (N, P and K) and micronutrients (Fe, Cu, Zn and Mn) content in wheat grains significantly varied among wheat cultivars. The macronutrients (N, P and K) and micronutrients (Fe, Cu and Mn) content in wheat grain and straw was non-significant due to spraying of Zn fertilizer irrespective of the source; however, Zn content in grain and straw varied significantly due to spraying of Zn fertilizer irrespective of the source. Whereas, the plant growth parameters and Zn content in succeeding moongbean was significantly higher with Zn @ 5 kg applied in soil as compared to other methods of Zn application. Therefore, it is recommended that soil application of 2.5 kg Zn ha-1 + 0.5% EDTA- Zn along with 1% urea at the time of booting + grain filling stages is required for enhanced the wheat grain quality (Zn content), however, soil application of Zn @ 5 kg ha-1 is beneficial for succeeding moongbean crop production between rice-wheat cropping system in the studied region.